2019
DOI: 10.1101/568535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetic lethality screening identifies FDA-approved drugs that overcome ATP7B-mediated tolerance of tumor cells to cisplatin

Abstract: Resistance of tumors to chemotherapy represents an important challenge in the modern oncology. Although platinum (Pt)-based drugs demonstrated excellent therapeutic potential their effectiveness in a wide range of tumors is limited by the development of resistance mechanisms. One of these mechanisms includes increased cisplatin sequestration/efflux by copper-transporting ATPase, ATP7B. In fact, ATP7B expression has been identified as a hallmark of chemotherapy-resistant tumors. However, targeting the ATP7B for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Moreover, it was shown that, in a breast cancer mouse model, tranilast treatment upregulates p53 and induces PARP and CASP3 cleavage in in vitro , consistent with the promotion of tumor cell apoptosis ( Subramaniam et al, 2010 ). In a recent work, through a synthetic lethality approach, the authors demonstrated that tranilast affects the expression of genes involved in several pathways that confer tolerance to cisplatin, including key platinum-transporting proteins such as ATOX1 ( Mariniello et al, 2020 ). In this regard, since Ca 2+ acts as a second messenger in several cell processes, gene expression modulation could reflect a TRPV2-mediated regulation of intracellular Ca 2+ levels ( De, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that, in a breast cancer mouse model, tranilast treatment upregulates p53 and induces PARP and CASP3 cleavage in in vitro , consistent with the promotion of tumor cell apoptosis ( Subramaniam et al, 2010 ). In a recent work, through a synthetic lethality approach, the authors demonstrated that tranilast affects the expression of genes involved in several pathways that confer tolerance to cisplatin, including key platinum-transporting proteins such as ATOX1 ( Mariniello et al, 2020 ). In this regard, since Ca 2+ acts as a second messenger in several cell processes, gene expression modulation could reflect a TRPV2-mediated regulation of intracellular Ca 2+ levels ( De, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed a correlation between elevated ATP7B expression and reduced effectiveness of cisplatin chemotherapy in cancer patients ( Miyashita et al, 2003 ; Nakayama et al, 2004 ). Consequently, targeted downregulation of ATP7B expression and trafficking is currently being explored as a potential strategy to increase the efficacy of cisplatin therapy ( Mangala et al, 2009 ; Mariniello et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it would be useful to develop an inhibitor, which affects both transporters, taking in account, however, that the impact of such inhibitor on the physiological functions of ATP7A and ATP7B has to be minimized. Interestingly, recent screening for FDA-approved drugs reducing tolerance to cisplatin revealed a compound, which suppresses ATOX1 expression and, as a consequence, ATP7B trafficking in a tumor-specific manner [61]. Considering that ATOX1 also supplies Cu/Pt to ATP7A, such compound would be promising for suppression of oncogenic activities of both ATP7A and ATP7B.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%